(untitled) (Journal of the College of Basic Education, 2022)
Research in the stages of childhood in all social, motor, emotional and mental aspects is one of the milestones that will indicate the crystallization of scientific awareness in society, and it leads to comprehensive objective ideas about man, his reality and his future.The twentieth century witnessed a great interest in studies and research that dealt with the study of the development and growth of children and the problems of this growth, and the researchers shed light on the development of the child in all its aspects. Social and its role in the child’s growth and upbringing (6: 22).The first half of the last century, especially during the third and fourth decades, also witnessed pioneering attempts to study the motor behavior of the child by Baylley, in 1935.